Improving accuracy in image-guided prostate biopsy by using trocar-sharpened needles - Kuru, Timur Hasan; Simpfendörfer, Tobias; Röthke, Matthias C.; Hohenfellner, Markus; Hadaschik, Boris (Urologia internationalis, 2013)
Objective: To optimize image-guided prostate biopsy by minimizing the target error with trocar-sharpened needle tips instead of beveled needles, which constantly deviate away from the bevel. Materials and Methods: We performed stereotactic biopsies on two prostate phantoms, which incorporate three randomly placed TRUS-visible lesions. Four stereotactic biopsies per lesion were taken under live-ultrasound guidance through a template: two biopsies with conventional beveled needles and two biopsies with novel trocar-sharpened needles. The procedural targeting error (PTE) between the virtually planned biopsy trajectory and the manually registered 3D needle position of every single biopsy core taken was calculated. Results: The absolute overall targeting error using the novel needle-tip design was 0.13 mm (SD: ± 0.15 mm) with the highest PTE in the sagittal plane (0.18 ± 0.16 mm), followed by the coronal (0.13 ± 0.17 mm) and axial (0.09 ± 0.05 mm) planes. Comparing the PTE of the novel trocar-shaped needles with conventional beveled needles, there was a statistically significant difference in the axial plane [p (overall) = 0.47, p(axial) = 0.03]. Conclusion: The targeting error of stereotactic biopsies using trocar-sharpened needles is significantly lower than the targeting error of classical beveled needles. Thus, trocar-tip configurations improve the accuracy of computer-assisted biopsies and allow precise assessment of suspicious lesions in the prostate and in other organs accessible to image-guided biopsy.
Gesehen am 21.07.2021